Ferroelectric nanofibers with an embedded optically nonlinear benzothiazole derivative - Batista, Rosa Maria Ferreira (2014)
We report measurements of the molecular first hyperpolarizability, thermal stability, photophysical, piezoelectric and ferroelectric properties of a benzothiazole derivative bearing an arylthiophene π-conjugated bridge both in solution and when embedded into a poly (L-lactic acid) (PLLA) matrix in the form of electrospun fibers with an average diameter of roughly 500 nm. The embedded nanocrystalline phenylthienyl-benzothiazole derivative, with crystal sizes of about 1.4 nm resulted in a good piezoelectric response from these functionalized electrospun fibers, indicative of a polar crystalline structure.